Androstenedione as a potential predictor of ovarian response in assisted reproductive technology programs - Anna G. Burduli; Natalia A. Kitsilovskaya; Yuliya V. Sukhova; Irina A. Vedikhina; Tatiana Yu. Ivanets; Vitaliy V. Chagovets; Nataliia L. Starodubtseva; Vladimir E. Frankevich (IP Berlin A.V., 2020)
Aim. To assess the possibility of using androstenedione levels in blood serum and follicular fluid to predict ovarian response in assisted reproductive technology programs and to conduct a comparative analysis of the results obtained by 2 methods chemiluminescent immunoassay (CLIA) and high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS). Materials and methods. A prospective study included 55 couples who received in vitro fertilization/intracytoplasmic sperm injection and embryo transfer program therapy. The patients were divided into 3 groups depending on the ovarian response to stimulation: 1st (13 oocytes, n=4), 2nd (49 oocytes, n=27), 3rd (over 10 oocytes, n=24). Androstenedione levels were measured in blood serum obtained on the day of transvaginal ovarian puncture and in follicular fluid samples with CLIA and HPLC-MS/ MS methods at the laboratories of Kulakov National Medical Research Center of Obstetrics, Gynecology and Perinatology. Results. On the day of transvaginal ovarian puncture, the serum androstenedione levels, which were measured by HPLC-MS/MS, were increasing with an increase of the number of oocytes obtained. The CLIA method revealed a difference in the androstenedione levels between the groups with the number of oocytes obtained of less than 3 and more than 10. Moreover, the androstenedione levels measured by CLIA were significantly different between the patient groups (p0.05). Comparison of serum androstenedione levels measured by CLIA and HPLC-MS/MS, showed high correlations between the values [=0.73 (p0.001)], which makes it possible to use both methods equally, given the existing equipment of the clinical base. Conclusion. Prediction of ovarian response to stimulation is an important step in assisted reproductive technology programs. Measuring androstenedione concentration in blood serum on the day of transvaginal ovarian puncture with highly specific methods (CLIA and HPLC-MS/MS) can be used to predict the degree of ovarian response along with the traditional assessment of the ovarian reserve based on determining anti-Mullerian hormone levels in the early follicular phase of the menstrual cycle.